Human induced pluripotent stem cell derived erythroblasts can undergo definitive erythropoiesis and co‐express gamma and beta globins. (16th May 2014) - Yang, Cheng‐Tao; French, Anna; Goh, Pollyanna Agnes; Pagnamenta, Alistair; Mettananda, Sachith; Taylor, Jenny; Knight, Sam; Nathwani, Amit; Roberts, David J.; Watt, Suzanne M.; Carpenter, Lee
Summary Human induced pluripotent stem cells (hiPSCs), like embryonic stem cells, are under intense investigation for novel approaches to model disease and for regenerative therapies. Here, we describe the derivation and characterization of hiPSCs from a variety of sources and show that, irrespective of origin or method of reprogramming, hiPSCs can be differentiated on OP9 stroma towards a multi‐lineage haemo‐endothelial progenitor that can contribute to CD144+ endothelium, CD235a+ erythrocytes (myeloid lineage) and CD19+ B lymphocytes (lymphoid lineage). Within the erythroblast lineage, we were able to demonstrate by single cell analysis (flow cytometry), that hiPSC‐derived erythroblasts express alpha globin as previously described, and that a sub‐population of these erythroblasts also express haemoglobin F (HbF), indicative of fetal definitive erythropoiesis. More notably however, we were able to demonstrate that a small sub‐fraction of HbF positive erythroblasts co‐expressed HbA in a highly heterogeneous manner, but analogous to cord blood‐derived erythroblasts when cultured using similar methods. Moreover, the HbA expressing erythroblast population could be greatly enhanced (44·0 ± 6·04%) when a defined serum‐free approach was employed to isolate a CD31+ CD45+ erythro‐myeloid progenitor. These findings demonstrate that hiPSCs may represent a useful alternative to standard sources of erythrocytes (RBCs) for future applications in transfusion medicine.